2022
DOI: 10.1177/01655515221110995
|View full text |Cite
|
Sign up to set email alerts
|

Finding answers to COVID-19-specific questions: An information retrieval system based on latent keywords and adapted TF-IDF

Abstract: The scientific community has reacted to the COVID-19 outbreak by producing a high number of literary works that are helping us to understand a variety of topics related to the pandemic from different perspectives. Dealing with this large amount of information can be challenging, especially when researchers need to find answers to complex questions about specific topics. We present an Information Retrieval System that uses latent information to select relevant works related to specific concepts. By applying Lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…By using text mining technique with LDA procedure to undertake an overview of a large body of coronavirus literature, Cheng et al [ 14 ] showed how information specialists could benefit the health and medical community. Chamorro-Padial et al [ 15 ] described an information retrieval system that chooses pertinent works associated with particular concepts using latent information. They found important ideas connected to a certain query and a corpus by using LDA models on COVID-19-related articles.…”
Section: Introductionmentioning
confidence: 99%
“…By using text mining technique with LDA procedure to undertake an overview of a large body of coronavirus literature, Cheng et al [ 14 ] showed how information specialists could benefit the health and medical community. Chamorro-Padial et al [ 15 ] described an information retrieval system that chooses pertinent works associated with particular concepts using latent information. They found important ideas connected to a certain query and a corpus by using LDA models on COVID-19-related articles.…”
Section: Introductionmentioning
confidence: 99%